2020
DOI: 10.1186/s12889-020-09207-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of public hospital managers’ risk and gain perception on their attitude towards physician dual practice: a cross-national study in 31 provinces of China

Abstract: Background: This study aims to explore the effect of public hospital managers' risk and gain perception on their attitude towards physician dual practice (PDP). Methods: A cross-sectional study enrolling 1513 managers from public hospitals in the East, Middle and West of China was conducted. Generalized linear mixed models (GLMM) were used to identify the determinants of managers' support for PDP. Results: The rate of managers' support for allowing PDP or implementing PDP with restriction, was 94.3% (95% CI: 0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The main motives for DP were seen as income enhancement followed by prestige and fringe benefits enjoyed in the public system. Yu et al (2020) studied the effect of public hospital managers' risk and gain perception on their attitude towards physician dual practice in China. The study found that the majority of Chinese public hospital managers are in favor of allowing or implementing PDP with restrictions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The main motives for DP were seen as income enhancement followed by prestige and fringe benefits enjoyed in the public system. Yu et al (2020) studied the effect of public hospital managers' risk and gain perception on their attitude towards physician dual practice in China. The study found that the majority of Chinese public hospital managers are in favor of allowing or implementing PDP with restrictions.…”
Section: Literature Reviewmentioning
confidence: 99%